If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(c+3)-2c-(1+3c)=20
We move all terms to the left:
(c+3)-2c-(1+3c)-(20)=0
We add all the numbers together, and all the variables
(c+3)-2c-(3c+1)-20=0
We add all the numbers together, and all the variables
-2c+(c+3)-(3c+1)-20=0
We get rid of parentheses
-2c+c-3c+3-1-20=0
We add all the numbers together, and all the variables
-4c-18=0
We move all terms containing c to the left, all other terms to the right
-4c=18
c=18/-4
c=-4+1/2
| 3(2r-6)=-27 | | 15=6-3m | | 3(z+6)-2z=-18 | | 2/5x+3=1/4x | | (2x+10)=30 | | 0.7=0.1*x+x | | 1/3(d+6)+3=1/4(4-d)-8 | | 7=2(3x-1) | | 12x+10-4+5x=176 | | -x13-2=3 | | -10m=10+7m | | 3(4+x)=x=6 | | -2-4a=-14 | | -20-6=12-8x | | 18=4(y+7)-6y | | -8.3=-3.5k+13.4 | | -31=-2x+7 | | 6e=-18 | | 5.3x-18=4.3x+2 | | 3b-4-3=11 | | r/4-3=3(4-2) | | 13x+15=26x+2 | | 15x-10=12x+50 | | 5x=x+122 | | 2(4z-9-7)=146-46 | | 12+4x-2=-10 | | 6b-5b-b+4b=16 | | 2-3(x+2)=44 | | 7y+2=102 | | -11x-38=127 | | -4x12=4 | | 4(2x+3)=6x-48 |